Urban biodiversity: Cuterebriasis in free-ranging Robinson’s mouse opossum (Marmosa robinsoni) in the suburbs of Barranquilla, Colombia (2023)
ABSTRACT: The tropical dry forest is one of the world’s most threatened ecosystems and is the habitat of the Robinson’s Mouse Opossum (Marmosa robinsoni), a small marsupial within the Didelphidae family. This study aimed to describe cases of cuterebriases in free-ranging M. robinsoni by examining individuals caught in live animal traps. Sherman traps were deployed in four different sites over three different periods in five days. All animals passed through biometry, weighing, sampling parasites, and sampling feces. Only animals captured in the study site located close to the city were anesthetized and examined. The evaluation included blood samples and a clinical examination. Animals received anesthesia under physical restraint by intramuscular injections of ketamine and xylazine. For anesthetic reversion, the protocol was Yohimbine administered before release. In total, 8% (5/60) of all captured animals had fly larvae extracted from wounds. The molecular Barcode of the mitochondrial Cytochrome Oxidase I gene showed no match with any recognized species of Cuterebra. The animals weighed from 35 to 80 g and had lesions in the scapular region with parasites under their skin in sizes ranging from 1.3 to 2.2 cm. The animals with parasites were in good physical condition without evidence of disturbances in health conditions. This is compatible with literature, reporting little effect on population dynamics of other host species infected with Cuterebra larvae. The study included 24 animals captured in three areas far from any city, which showed no evidence of cuterebrid infection, suggesting that proximity to the city could increase exposure to cuterebriasis. There are reports of cuterebrids in M. robinsoni in Brazil; however, this is the first report of cuterebriasis in M. robinsoni in Colombia.